Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

EdTech for Ugandan girls: Affordances of different technologies for girls' secondary education during the Covid-19 pandemic - Damani, Kalifa; Daltry, Rebecca; Jordan, Katy; Hills, Libby; Evans, Laura (Development Policy Review, 2022)
Motivation This article discusses the use of educational technology (EdTech) in girls' education at PEAS (Promoting Education in African Schools) schools in rural Uganda during the Covid-19-related school closures. Purpose This article addresses a research gap surrounding the potential use of EdTech to support girls' education, focusing on the barriers to girls' EdTech use and how technology might be used to enhance girls' education in disadvantaged rural areas—specifically their academic learning and their social and emotional learning. Methods and approach A sequential, explanatory mixed-methods case-study approach was used. Quantitative exploration of a dataset of 483 Ugandan students, from 28 PEAS schools, was first conducted, followed by interviews with PEAS staff to elucidate the reasons and context behind the findings. Findings Findings show that female students are less likely than male students to have access to their caregivers' phones for learning. The form of EdTech that appeared to be most beneficial for girls' academic learning was radio; girls also had significantly more interest in tuning into radio broadcasts than boys did. Also, poorer boys were more likely to be influenced by SMS messages than wealthier boys. Apart from gender-based differences, students with more highly educated parents found SMS messages more helpful, and phone calls from teachers appeared to help boost younger students' self-confidence. Policy implications The findings suggest that policy-makers need to: carefully consider provision of education through multiple modes of EdTech in order to ensure that it reaches all students; ensure that caregivers are involved in the strategies developed for girls' education; make EdTech interventions interactive; and consider language in EdTech interventions. Given the gender differences which emerged, the findings are of relevance both to supporting the continuation of educational provision during periods of school closure, and also in terms of finding additional ways to support girls' education alongside formal schooling.
Keywords: Covid-19; EdTech; education; gender; rural Uganda

Bandarban Sandbox: Needs assessment and hypothesis development - Tanweer, Rabia; Nashtaran, Trishia; Plaut, Daniel; Rahman, Asad; Ahmed, Shakil; Chowdhury, Dilruba; Rabbi, BM Fazley; Hoque, Rashedul; Nahar, Nurun; Afroze, Sadia (EdTech Hub, 2022)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners, working closely with the government and EdTech Hub to identify how EdTech can best be harnessed to support learning in Bangladesh. This partnership uses the sandbox approach — which provides a space for partners to test and grow ideas in conditions of uncertainty — to test how EdTech modalities that aim to improve numeracy outcomes for Grade 6 learners (early secondary) in Bandarban, one of the most remote areas of Bangladesh, can be used most effectively by learners and educators. This report outlines the process and findings from the needs assessment and hypothesis development phase. These findings (as well as the data collection which informs them) are organised around five research questions developed by EdTech Hub in partnership with Agami Education Foundation, the implementing agency for the sandbox. The findings of the research were distributed in themes that outlined the availability and utilisation of technology and a valid level of knowledge and interest in teachers and students towards using technology for education. While some findings shed light on the technical aspects of the context, some human factors also played a role in resisting the acceptance of technology in education. Building on the learning from this needs assessment phase, Agami Education Foundation and EdTech Hub have agreed to test this implementation plan in the upcoming staggered deployment phase. Keywords: EdTech; sandbox; numeracy; Bandarban; Bangladesh; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen